2013
DOI: 10.1302/0301-620x.95b7.31316
|View full text |Cite
|
Sign up to set email alerts
|

Under-coracoid-around-clavicle (UCAC) loop in type II distal clavicle fractures

Abstract: In Neer type II (Robinson type 3B) fractures of the distal clavicle the medial fragment is detached from the coracoclavicular ligaments and displaced upwards, whereas the lateral fragment, which is usually small, maintains its position. Several fixation techniques have been suggested to treat this fracture. The aim of this study was to assess the outcome of patients with type II distal clavicle fractures treated with coracoclavicular suture fixation using three loops of Ethibond. This prospective study include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
(37 reference statements)
2
23
0
2
Order By: Relevance
“…This was largely because such fractures are rare. However, the results were comparable to the main other research [12][13][14].The clinical significance of this study lies in the observation that the loop plate-suture technique can be adopted as a considerable choice for the treatment of Neer type IIB distal clavicle fracture. Besides, it also provides an inspiring functional outcome and allows arthroscopic treatment of associated lesions in the procedure without requiring later implant removal.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This was largely because such fractures are rare. However, the results were comparable to the main other research [12][13][14].The clinical significance of this study lies in the observation that the loop plate-suture technique can be adopted as a considerable choice for the treatment of Neer type IIB distal clavicle fracture. Besides, it also provides an inspiring functional outcome and allows arthroscopic treatment of associated lesions in the procedure without requiring later implant removal.…”
Section: Discussionsupporting
confidence: 81%
“…In recent years, scholars have attempt to apply loop plate and suture technique to get anatomic reconstruction of acromioclavicular joint through elastic compression fixation at clavicle and coracoid process [11][12]. Most of them performed single-bundle reconstruction of coracoclavicular ligament.…”
Section: Discussionmentioning
confidence: 99%
“…Simple isolated coracoclavicular fixation with Mersilene tape, Ethibond sutures, titanium cables, dacron graft neutralizes the displacement and brings the fracture fragments together and have shown good functional outcomes with few minor complications. 13 Fixation with K wires and applying a tension band is an age old technique for distal clavicle fracture. Kona et al reported poor results in 10 of 19 patients, with 6 nonunions and 5 infections.…”
Section: Discussionmentioning
confidence: 99%
“…Existen diversas técnicas quirúrgicas para el tratamiento de las fracturas desplazadas de clavícula distal donde se describen distintos sistemas de fijación, entre ellos: la placa clavicular con gancho, lazo entre clavícula y coracoides, botones corticales similares a los usados en disyunción acromioclaviculares, fijación con bandas de tensión, cables de titanio, tornillos acromioclaviculares y tornillos coracoclaviculares. 5,[7][8][9][10][11][12][13] Además, éstas pueden ser abordadas de manera convencional, artroscópica o mínimamente invasiva con resultados similares reportados en la literatura internacional. [7][8][9][10][11][14][15][16] En el último tiempo, las técnicas mínimamente invasivas han aparecido de manera importante en la cirugía traumatológica debido a los beneficios que conlleva, siendo los principales un menor tiempo quirúrgico, menor daño de partes blandas y cicatrices pequeñas con mejor estética.…”
Section: Introductionunclassified
“…5,[7][8][9][10][11][12][13] Además, éstas pueden ser abordadas de manera convencional, artroscópica o mínimamente invasiva con resultados similares reportados en la literatura internacional. [7][8][9][10][11][14][15][16] En el último tiempo, las técnicas mínimamente invasivas han aparecido de manera importante en la cirugía traumatológica debido a los beneficios que conlleva, siendo los principales un menor tiempo quirúrgico, menor daño de partes blandas y cicatrices pequeñas con mejor estética. El uso de los botones corticales se ha propuesto como un método mínimamente invasivo para fijar y estabilizar las fracturas desplazadas de clavícula distal, existiendo estudios que muestran excelentes resultados clínicos.…”
Section: Introductionunclassified